Thalamus volume change and cognitive impairment in early relapsing–remitting multiple sclerosis patients - Rojas, Juan Ignacio (2018)
Aims: The objective of the study was to assess whether changes in the volume of the thalamus during the onset of multiple sclerosis predict cognitive impairment after accounting for the effects of brain volume loss. Methods: A prospective study included patients with relapsing–remitting multiple sclerosis less than 3 years after disease onset (defined as the first demyelinating symptom), Expanded Disability Status Scale of 3 or less, no history of cognitive impairment and at least 2 years of follow-up. Patients were clinically followed up with annual brain magnetic resonance imaging and neuropsychological evaluations for 2 years. Measures of memory, information processing speed and executive function were evaluated at baseline and follow-up with a comprehensive neuropsychological test battery. After 2 years, the patients were classified into two groups, one with and the other without cognitive impairment. Brain dual-echo, high-resolution three-dimensional T1-weighted magnetic resonance imaging scans were acquired at baseline and every 12 months for 2 years. Between-group differences in thalamus volume, total and neocortical grey matter and white matter volumes were assessed using FIRST, SIENA, SIENAXr, FIRST software (logistic regression analysis P < 0.05 significant). Results: Sixty-one patients, mean age 38.4 years, 35 (57%) women were included. At 2 years of follow-up, 17 (28%) had cognitive impairment. Cognitive impairment patients exhibited significantly slower information processing speed and attentional deficits compared with patients without cognitive impairment (P < 0.001 and P = 0.02, respectively). In the cognitive impairment group a significant reduction in the percentage of thalamus volume (P < 0.001) was observed compared with the group without cognitive impairment. Conclusion: We observed a significant decrease in thalamus volume in multiple sclerosis-related cognitive impairment.